Kibun Daizin; Or, From Shark-Boy to Merchant Prince - Murai, Gensai, 1864-1927; Varian, George, 1865-1923; Yoshida, Masao (Salt Lake City, UT : Project Gutenberg, 2021)
"Kibun Daizin; Or, From Shark-Boy to Merchant Prince" by Gensai Murai is a historical novel written in the early 20th century. The story revolves around the ambitious character Bunkichi, a young boy who dreams of becoming the leading merchant in Japan, inspired by his father's wishes for him to uphold their family honor. As he embarks on this journey, the narrative explores themes of courage, ambition, and the spirit of enterprise in the face of adversity. The opening of the book introduces Bunkichi as he approaches the master of the Daikokuya shop, seeking apprenticeship. He explains his desire to rise from humble beginnings to a position of respect and wealth. As he shares his life story, detailing the hardships of losing his parents and his vow to become a successful merchant, he demonstrates not only his determination but also his ingenuity when confronted with the peril of a shark terrorizing the waters near Kumano. Bunkichi's fearless plans to defeat the shark and secure his place among the best merchants mark the beginning of an adventurous journey fueled by dreams and willingness to take risks, captivating readers with his tenacity and the rich backdrop of 18th-century Japan. (This is an automatically generated summary.)
Release date is 2021-05-11
Mary Glenn Krause, Charlene Taylor, Barry Abrahamsen, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Japan -- Fiction